EDUCATIONAL GAME HIJAIYAH LETTER INTRODUCTION FOR DEAF IMPAIRMENT AND MENTALLY DISABILITIES CHILDREN - Fatah Yasin Al Irsyadi; Dedi Gunawan; Avifah Hasna Nur Fadila; Yogiek Indra Kurniawan (Informatika, Universitas Jenderal Soedirman, 2022)
Sekolah Luar Biasa (SLB) Yayasan Asuh Anak-Anak Tuna(YAAT) Surakarta is a school that focuses on educating children with deaf impairment and mentally retarded disabilities in Surakarta. Less interest in learning and the lack of alternative learning media are problems that arise in the school, one of which is regarding the learning of hijaiyah letters. The purpose of this research is to provide a solution for schools to deal with existing problems by developing educational games to increase interest in learning for deaf and mentally retarded students and to become an alternative learning medium for teachers to students. This game was designed using Construct 2 software and for its manufacture using several steps, such as Analysis, Application Design, Application Implementation, and Testing. This game is made as easy as possible so that students can easily use it. The built application consists of several menus, namely materials, playing and quizzes. After the application has been demonstrated, the game is played by students alternately, then students and teachers are given a questionnaire to test the performance and usability of the game. The results of the blackbox test showed that the application was in accordance with what was expected by the application developer, and the results of the User Acceptance Test obtained an average value of 91.908%, indicating that this game makes it easier for teachers to convey material and provides convenience for students in understanding learning material.